The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1073/pnas.1413983111
|View full text |Cite
|
Sign up to set email alerts
|

Full-length structure of a monomeric histidine kinase reveals basis for sensory regulation

Abstract: Although histidine kinases (HKs) are critical sensors of external stimuli in prokaryotes, the mechanisms by which their sensor domains control enzymatic activity remain unclear. Here, we report the full-length structure of a blue light-activated HK from Erythrobacter litoralis HTCC2594 (EL346) and the results of biochemical and biophysical studies that explain how it is activated by light. Contrary to the standard view that signaling occurs within HK dimers, EL346 functions as a monomer. Its structure reveals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(113 citation statements)
references
References 41 publications
(54 reference statements)
9
100
0
Order By: Relevance
“…8D). This is consistent with findings that although some LOV-HisKAs follow a "tilting/rotation" model in which light induces modest structural changes, some members are known to be monomeric or stably oligomeric in the dark (4,(58)(59)(60)(61)(62) and thus are possibly less constrained with respect to sensor-effector orientation. The observed spread per linker band may reflect subpopulations of LOV-HisKAs.…”
Section: Resultssupporting
confidence: 90%
“…8D). This is consistent with findings that although some LOV-HisKAs follow a "tilting/rotation" model in which light induces modest structural changes, some members are known to be monomeric or stably oligomeric in the dark (4,(58)(59)(60)(61)(62) and thus are possibly less constrained with respect to sensor-effector orientation. The observed spread per linker band may reflect subpopulations of LOV-HisKAs.…”
Section: Resultssupporting
confidence: 90%
“…Experimental structures exist for three of the four subfamilies revealing a similar fold, with monomers forming two antiparallel helices connected by a loop region. The DHp domain typically forms a stable homodimer revealing a four-helix bundle architecture; to the contrary the single existing HisKA_2 structure reveals a functional monomeric architecture [75]. Despite the similarities in structure we caution that based on current evidence the separation into different sequence families appears to reflect differences in mechanism of autophosphorylation as discussed below.…”
Section: Kinase Activationmentioning
confidence: 99%
“…In these HK signal dependent activation occurs through conformational changes within the homodimer. In contrast, a recent study demonstrated that the HisKA_2-type kinase EL346 from Erythrobacter litoralis exists as a monomer and that signal detection and signal mediated activation does not require dimerization [75]. Instead the structure of this protein suggests an activation mechanism where a blue light sensitive LOV domain competes with the CA domain for the phosphorylatable histidine residue on the DHp domain.…”
Section: Kinase Activationmentioning
confidence: 99%
“…SasA has been shown by analytical ultracentrifugation to form a trimer in solution (65), and gel filtration experiments support a stoichiometry of one SasA trimer per KaiC hexamer. HKs usually oligomerize as dimers, but in rare cases have been found to function as higher order oligomers (66) or monomers (67). It is yet unknown whether this unusual oligomeric state for SasA is linked to its sensory function.…”
Section: Kaib: Attenuator Of Kaic Phosphorylationmentioning
confidence: 99%